Assessment of the prevalence of burnout and well‐being in solid organ transplant pharmacists. Issue 8 (2nd June 2022) - Harris, Matt; Pilch, Nicole; Doligalski, Christina T.; Henricksen, Erik; Melaragno, Jennifer; Lichvar, Alicia
Abstract: Background: Solid organ transplant (SOT) pharmacist burnout and well‐being has not been described. Methods: A survey of SOT pharmacists was distributed to transplant pharmacy organization listservs. Burnout was assessed with the full 22 item Maslach Burnout Inventory Human Services Survey for Medical Personnel (MBI‐HSS‐MP) and well‐being was assessed with the Mayo Well‐Being Index (WBI). Logistic multivariate regression was constructed to identify risk factors for a composite burnout assessment. Results: In total, 230 responses were included (estimated response rate 36.2%). Survey participants were predominantly Caucasian (80.4%), female (79.1%), married/partnered (67.4%), and were within the first 5 years of practice (32.2%) as clinical pharmacist/specialists (87%). According to the MBI‐HSS‐MP, 63% met criteria for burnout. Comparing the groups with or without burnout, low quality of life (40.4% vs. 9.5%; P <.001), extreme fatigue (52.1% vs. 19%; P <.001), and likelihood of leaving the job for reasons other than retirement (38.5% vs. 10.7%; P <.001) were more common. The incidence of SOT pharmacists with WBI scores ≥ 5 (decreased well‐being) was 26.5%. Among clinical pharmacists, risk factors for burnout included > 10 h per week of clinical duties outside of transplant (OR 2.669, P = .021) and extreme fatigue (OR 3.473, P <.001). Conclusions: Pharmacist burnout in SOT practice was similar to that reported in various pharmacy specialties (53–61%), which impacts clinical workforce retention and personal well‐being.